2004
DOI: 10.1007/s00421-003-1031-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of creatine supplementation on muscular performance and body composition responses to short-term resistance training overreaching

Abstract: To determine the effects of creatine supplementation during short-term resistance training overreaching on performance, body composition, and resting hormone concentrations, 17 men were randomly assigned to supplement with 0.3 g/kg per day of creatine monohydrate (CrM: n=9) or placebo (P: n=8) while performing resistance exercise (5 days/week for 4 weeks) followed by a 2-week taper phase. Maximal squat and bench press and explosive power in the bench press were reduced during the initial weeks of training in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 42 publications
4
63
1
4
Order By: Relevance
“…1915;Hunter 1922). Cr supplementation has been reported to improve physical performance during a variety of different exercise modalities, intensities and durations and to promote greater gains in strength, muscle mass, bone mineral density and neuromuscular function in populations ranging from trained healthy individuals to the elderly with sarcopenia undergoing exercise rehabilitation (Bosco et al 1997;Grindstaff et al 1997;Mihic et al 2000;Metzl et al 2001;Mihic et al 2000;Hespel et al 2001;Volek et al 2004;Pearlman and Fielding, 2006;Bazzucchi et al 2009;Bemben et al 2010;Devries and Phillips, 2014;Gualano et al 2011;Gualano et al 2014;Candow et al 2015;Chillibeck et al, 2015;Griffen C et al 2015;Martone et al 2015;Ramirez-Campilo et al, 2015;Wilkinson et al 2015, Phillips, 2015 (see Table 1). The mechanism(s) responsible for these effects range from Cr-induced increases in intramuscular phosphocreatine (PCr) levels and the PCr/ATP energy charge ratio, as well as a greater resynthesis rate of PCr following intense exercise, leading to a higher efficiency of ATP utilisation (Wallimann et al 2011) and to attenuated cardiovascular and thermoregulatory responses during prolonged exercise in the heat (Demant and Rhodes, 1999;Terjung et al 2000;Lopez et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1915;Hunter 1922). Cr supplementation has been reported to improve physical performance during a variety of different exercise modalities, intensities and durations and to promote greater gains in strength, muscle mass, bone mineral density and neuromuscular function in populations ranging from trained healthy individuals to the elderly with sarcopenia undergoing exercise rehabilitation (Bosco et al 1997;Grindstaff et al 1997;Mihic et al 2000;Metzl et al 2001;Mihic et al 2000;Hespel et al 2001;Volek et al 2004;Pearlman and Fielding, 2006;Bazzucchi et al 2009;Bemben et al 2010;Devries and Phillips, 2014;Gualano et al 2011;Gualano et al 2014;Candow et al 2015;Chillibeck et al, 2015;Griffen C et al 2015;Martone et al 2015;Ramirez-Campilo et al, 2015;Wilkinson et al 2015, Phillips, 2015 (see Table 1). The mechanism(s) responsible for these effects range from Cr-induced increases in intramuscular phosphocreatine (PCr) levels and the PCr/ATP energy charge ratio, as well as a greater resynthesis rate of PCr following intense exercise, leading to a higher efficiency of ATP utilisation (Wallimann et al 2011) and to attenuated cardiovascular and thermoregulatory responses during prolonged exercise in the heat (Demant and Rhodes, 1999;Terjung et al 2000;Lopez et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated positive effects (VOLEK; BRANCH, 1998;VOLEK et al, 2004;RINGEL et al, 2008;DILGER et al, 2013), while others did not observe changes (LOUIS et al, 2003). A study developed by the EFSA Journal (2009) with 1-to 42-dayold broilers, using a pelleted vegetable diet (corn/ wheat/soybean meal), supplemented with 0 to 800 continuation mg GAA per kg of diet, improved weight gain with supplementation of between 400 and 800 mg kg -1 , while feed conversion was significantly improved from 400 mg kg -1 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that there are benefits to enhancing the skeletal muscle store of creatine. These include improved maintenance of maximal power outputs, 1,2,4,5,17,18,31 more rapid recovery from high-intensity exercise, 14,15,27,35,36 and diminished post-exercise muscular pain. 35,36 Creatine supplementation in combination with high-intensity exercise training has been shown to improve short-term power output, and is reportedly most beneficial for maximising repeated high-intensity work performance.…”
Section: 2436mentioning
confidence: 99%